2021
DOI: 10.3390/ijerph18126558
|View full text |Cite
|
Sign up to set email alerts
|

Combined Exposure to Metals in Drinking Water Alters the Dopamine System in Mouse Striatum

Abstract: Environmental exposure to arsenic (As), lead (Pb), and cadmium (Cd) frequently occurs; however, data on the specific effects of combined exposure on neurotransmission, specifically dopaminergic neurotransmission, are lacking. In this study, motor coordination and dopamine content, along with the expression of tyrosine hydroxylase (TH), dopamine transporter (DAT), vesicular monoamine transporter 2 (VMAT2), and dopamine receptors (DRs), were examined in the striatum of adult male mice following exposure to drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…In the current study, the lead-exposed group exhibited a significant decrease ( p = 0.001) in the brain dopamine content compared with the control group. These observations agree with those of previous investigators [ 42 , 68 ]. However, an earlier study has reported increase in dopamine levels following lead exposure [ 69 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the current study, the lead-exposed group exhibited a significant decrease ( p = 0.001) in the brain dopamine content compared with the control group. These observations agree with those of previous investigators [ 42 , 68 ]. However, an earlier study has reported increase in dopamine levels following lead exposure [ 69 ].…”
Section: Discussionsupporting
confidence: 94%
“…Differences in exposure levels and duration may account for this discrepancy. The reduced dopamine concentration may be attributed to the downregulation of tyrosine hydroxylase, which is a dopamine biosynthesis enzyme, resulting in a decline in dopamine production [ 68 ]. Of note, co-treatment with the A. maurorum extract restored the dopamine concentration to the normal level, thus reversing the neurobehavioral impairments induced by lead exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may also explain the more pronounced motor and cognitive decline observed in the metal mixture exposure group than in the single metal exposure groups. Similar results have been reported in other studies, demonstrating that exposure to metal mixtures can alter dopamine levels, resulting in behavioral dysfunction (37,51). The gene encoding TH, the rate-limiting enzyme in dopamine biosynthesis, was significantly downregulated in the PHC group compared to the control group of the present study.…”
Section: Discussionsupporting
confidence: 92%
“…C57BL/6 mice were administered the metals individually or in combination through their drinking water because this route reflects a common mode of metal exposure in humans (36). The administered doses were determined based on previous studies and WHO guidelines for drinking water (37). Behavioral tests were performed to assess neurobehavioral dysfunction, and changes in the neurotransmitter systems in the striatum were analyzed to elucidate the underlying mechanisms of action.…”
Section: Introductionmentioning
confidence: 99%
“…[29] In a recent study, exposure to a metal mixture containing Pb, As, and Cd impaired the motor coordination and significantly reduced the dopamine levels and expression of tyrosine hydroxylase (Th), dopamine transporter, and vesicular monoamine transporter 2 in the striatum of mice; however, the expression of dopamine receptors were not significantly changed. [32] In another study, the authors reported that the toxic effects of heavy metal mixture (Pb, Cd, and Hg) in the brain of albino rats are induced by oxidative stress and inflammation as evident by the increased lipid peroxidation and proinflammatory cytokines (interleukin [IL]-6), and decreased levels of antioxidants (superoxide dismutase, catalase, and glutathione) and anti-inflammatory cytokines (IL-10). Further, the metal mixture caused the histological perturbations, which included reactive gliosis and glia cell proliferation.…”
Section: Neurological Disordersmentioning
confidence: 99%